Evaluasi Kebijakan Pelestarian Terumbu Karang di Polewali Mandar Tahun 2012 - Rizqa Audian Pratiwi; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2014)
Abstract :This is study about Evaluation of the Coral Reef Conservation Policyconducted by the Local Government of Polewali Mandar which began in 2005based on the policy of the central government through the Coral ReefRehabilitation and Management (Coral Reef Rehabilitation and ManagementProject) or COREMAP. The high degradation of coral reefs in Indonesia,especially in Polewali Mandar. Damage to coral reef decline in the impact offisheries production and reduced the income of fishermen. The data for this studywere collected using interviews, library research and documentation of relatedagencies and coastal communities. This study aims to determine how theimplementation of conservation policies and the extent to which the results of theimplementation of the policy runs after 7 years in implementing the goals of theindicators that have been defined previously.Keywords : policies, conservation, coral reefs